2013
DOI: 10.1186/2049-9957-2-31
|View full text |Cite
|
Sign up to set email alerts
|

Chinese social media reaction to the MERS-CoV and avian influenza A(H7N9) outbreaks

Abstract: BackgroundAs internet and social media use have skyrocketed, epidemiologists have begun to use online data such as Google query data and Twitter trends to track the activity levels of influenza and other infectious diseases. In China, Weibo is an extremely popular microblogging site that is equivalent to Twitter. Capitalizing on the wealth of public opinion data contained in posts on Weibo, this study used Weibo as a measure of the Chinese people’s reactions to two different outbreaks: the 2012 Middle East Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
108
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(111 citation statements)
references
References 31 publications
2
108
0
1
Order By: Relevance
“…The medium strength of the correlation between the amount of online news articles and the amount of Weibo posts or the amount of Baidu searches suggested that that user-generated content could have been driven by other sources in addition to media. For instance, on social media, posts by important opinion leaders were found to be very influential [32]. It would be interesting for future research to investigate sources other than media that can impact online public opinions, especially in the case of a vaccine crisis.…”
Section: Discussionmentioning
confidence: 96%
“…The medium strength of the correlation between the amount of online news articles and the amount of Weibo posts or the amount of Baidu searches suggested that that user-generated content could have been driven by other sources in addition to media. For instance, on social media, posts by important opinion leaders were found to be very influential [32]. It would be interesting for future research to investigate sources other than media that can impact online public opinions, especially in the case of a vaccine crisis.…”
Section: Discussionmentioning
confidence: 96%
“…Almost all cases were hospitalized, and 158 (36%) died. The majority of cases [309 [19][20][21][22][23][24][25], and a more equal sex distribution (56% male cases) (27). The reasons for the predominance of older male cases are not understood but have been attributed to cultural practices in which older men may be more likely to shop at LPMs.…”
Section: Epidemiology Of H7n9mentioning
confidence: 92%
“…Clinician and public awareness for symptoms and testing was raised through traditional and social media such as Weibo, the Chinese equivalent to Twitter (25). Improvements in these systems, along with significant progress in use of polymerase chain reaction (PCR) and sequencing by the China CDC, contributed to the rapid characterization of H7N9 cases.…”
Section: Epidemiology Of H7n9mentioning
confidence: 99%
“…One avenue could be social media. Microblogging sites are very popular in China, and whilst they are increasingly being used by epidemiologists and researchers to measure public awareness and reactions to outbreaks of infectious diseases, this approach could be similarly used by authorities to facilitate public health communication messages (Fung et al., ). Health promotion strategies need to acknowledge cultural differences and education levels between, for example, urban and poor rural populations.…”
Section: Discussionmentioning
confidence: 99%